Avaliação transanestésica do gradiente de temperatura centro-periférico e da eficácia do tramadol preemptivo no controle da dor pós-operatória em ratos - (:unkn) unknown (Universidade Federal do Pampa, 2024)
This study aimed to determine the efficacy of preemptively administered subcutaneous tramadol in postoperative analgesia in rats undergoing medial knee arthrotomy with cranial cruciate ligament transection. Additionally, the study investigated the values of the center-peripheral temperature gradient (ΔTcp) in rats anesthetized with isoflurane. A total of 48 rats underwent the surgical procedure, and it was observed that preemptive tramadol was effective in controlling acute postoperative pain. The temperature gradient varied during the anesthetic procedure, being higher at the beginning and reduced by the end of anesthesia.
Transanesthetics evaluation of the center-peripheral temperature gradient and the efficacy of preemptive tramadol in controlling postoperative pain in rats
Keywords: Roedores; Opioides; Temperature; Hypothermia; Opioids; Analgesia; Rodents; Hipotermia; Analgesia; Temperatura; CNPQ::CIENCIAS AGRARIAS